2009
DOI: 10.1523/jneurosci.3633-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Use of Two Behavioral Mechanisms for Chemotaxis inCaenorhabditis elegans

Abstract: Caenorhabditis elegans shows chemotaxis to various odorants and water-soluble chemoattractants such as NaCl. Previous studies described the pirouette mechanism for chemotaxis, in which C. elegans quickly changes the direction of locomotion by using a set of stereotyped behaviors, a pirouette, in response to a decrease in the concentration of the chemical. Here, we report the discovery of a second mechanism for chemotaxis, called the weathervane mechanism. In this strategy animals respond to a spatial gradient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
361
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(432 citation statements)
references
References 27 publications
25
361
1
2
Order By: Relevance
“…First, we examined the statistics of run duration, the time intervals between successive reorientation maneuvers. As before for negative thermotaxis, we found that worms exhibited longer runs when headed down gradients than up gradients (11)(12)(13)21) (Fig. 2C).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…First, we examined the statistics of run duration, the time intervals between successive reorientation maneuvers. As before for negative thermotaxis, we found that worms exhibited longer runs when headed down gradients than up gradients (11)(12)(13)21) (Fig. 2C).…”
Section: Resultssupporting
confidence: 82%
“…Steering mechanisms (also called weathervaning) have been identified in C. elegans chemotaxis (11,21,22). To look for steering mechanisms, we focused on runs pointed orthogonally to the gradient.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has shown that worms use a klinokinesis strategy, where frequency of reversal is changed depending on the concentration of stimuli, when aerotaxing in the absence of food (29). This strategy resembles that used by worms chemotaxing to other cues such as salts and odors (26,30). Our quantitative experiments show that the URX oxygen sensors evoke reversals in response to O 2 stimuli that have only minor effects on speed.…”
Section: Discussionsupporting
confidence: 54%
“…1D and Movie S1). These combined strategies would allow C. elegans to move efficiently to its preferred humidity level (16,17). In contrast, control worms assayed in the absence of a humidity gradient (with both troughs empty) showed no preference (Fig.…”
Section: Significancementioning
confidence: 99%